Date rape the agricultural and astronomical background of the Sumerian sacred marriage and Genesis 38 - Homan, Michael M. (2002)
The differentiated sexuality of the date palm and its artificial fertilization were the subject of many ancient Near Eastern myths. This paper argues that much of the Sumerian sacred marriage between Inanna and Dumuzi celebrated during the spring New Year is an anthropomorphization of the date palm's artificial fertilization and vernal astronomical observations. The story of Judah and Tamar in Genesis 38 is also argued to have originated from the same source.
Keywords: Tamar -- Schwiegertocher Judas, Biblische Person; Bibel; Astronomie